(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
Consistency is one of the most important physical properties of fats since it is directly associated with its several applications. This property can be considered an important functional aspect of the plastic fats, which are a mixture of solid and liquid fat phase. The fat solid phase forms a tridimentional lattice arising plasticity to the fat. The objective of this paper was to analyze the interactions that occur in binary mixtures of two animal fats (abdominal chicken fat and bacon fat), regarding their consistency at different temperatures. The samples were analyzed for the fatty acid composition and for the consistency at the temperatures of 10 to 25 ºC. The texture analyzer TA-XT2 (Stable Micro Systems) was utilized. A mathematical model of multiple regression of the quadratic type was applied. The results showed that the eutectic effect was observed between the binary mixtures of stearins and bacon fat. On the other hand, mixtures between abdominal chicken fat and bacon fat showed a synergic effect (compound formation).